Vaccines and therapeutics for immunocompromised patients with COVID-19 - Shoham, Shmuel; Batista, Carolina; Ben Amor, Yanis; Ergonul, Onder; Hassanain, Mazen; Hotez, Peter; Kang, Gagandeep; Kim, Jerome H.; Lall, Bhavna; Larson, Heidi J.; Naniche, Denise; Sheahan, Timothy; et al. (EClinicalMedicine, 2023)
The COVID-19 pandemic has disproportionately impacted immunocompromised patients. This diverse group is at increased risk for impaired vaccine responses, progression to severe disease, prolonged hospitalizations and deaths. At particular risk are people with deficiencies in lymphocyte number or function such as transplant recipients and those with hematologic malignancies. Such patients’ immune responses to vaccination and infection are frequently impaired leaving them more vulnerable to prolonged high viral loads and severe complications of COVID-19. Those in turn, have implications for disease progression and persistence, development of immune escape variants and transmission of infection. Data to guide vaccination and treatment approaches in immunocompromised people are generally lacking and extrapolated from other populations. The large clinical trials leading to authorisation and approval of SARS-CoV-2 vaccines and therapeutics included very few immunocompromised participants. While experience is accumulating, studies focused on the special circumstances of immunocompromised patients are needed to inform prevention and treatment approaches.